Pengendalian Mutu Produk Croissant Chocolate Menggunakan Metode Statistical Quality Control (SQC) di PT. Bapak Bakery - Bertie, Dorothy Alma; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 11 No 2 (2023): JuniDO - 10.24843/JRMA.2023.v11.i02.p05, 2023)
One of the products of PT. Bapak Bakery which has the highest market demand is the chocolate croissant. The large demand for this product results in a large number of reject products that are not in accordance with company standards. Therefore, it is necessary to study the production process and quality control using the Statistical Quality Control (SQC) method so that it can be seen whether the number of reject products in this product is still within the company's tolerance limits or not. The purpose of this research is to study the production process and product quality aspects of chocolate croissant PT. Bapak Bakery. The method used in this research is field practice, observation, interviews, literature study, and data processing. In the production process of chocolate croissants at PT. Bapak Bakery is carried out through several stages, namely the preparation of ingredients, weighing of ingredients, mixing, weighing the dough, freezing the dough, sheeter, cutting, filling with chocolate sticks, forming, proofing, greasing, baking, resting, and packaging. The results of the analysis using the Statistical Quality Control (SQC) method showed that the total chocolate croissants reject products were 269 pcs with details as many as 139 pcs (52%) experiencing burnt rejects (overcooked) and as many as 130 pcs (48%) experiencing reject layers that did not come out of the total. 1966 pcs chocolate croissants produced during the research period. The results of the analysis using the SQC method indicate that the number of reject products is still within the tolerance limits set by the company. Two causes of chocolate croissant damage are found in the machine factor, the worker factor, the raw material factor, and the method used during the production process. Keywords: Quality Control, Statistical Quality Control (SQC), Croissant, PT. Bapak Bakery